Faktor Keterlambatan Berbicara Pada Anak Usia 4-5 Tahun Pada Masa COVID-19 (Tinjauan Literatur) - Davina Salsabilla Saragi; Mira Rahmawati; Nur Aini Sekar Pitaloka; Salsabila Bunga Intan Permata; Niken Aulia; Fadilatul Ulum; Ummu Hani' Habibah (Academica: Journal of Multidisciplinary Studies, 2023)
One of the things that can interfere child development is speech delayed. Speech delay is a condition in which children experience delays in language development and speaking skills according to their age. This study aims to identify the factors that affect speech delays in early childhood during the COVID-19 pandemic. This study use literature review, descriptive qualitative approach. The data of this research were taken from Google Scholar. The results show that COVID-19 pandemic has had a significant impact on various aspects of life, including language development in children. The social distancing regulation from the government requires children to do activities at home. It increase the “screen time” and caused lack interaction between children and their families. Parents play an important role in preventing speech delay in children by limiting the use of gadgets and strengthening family interactions to prevent and overcome speech delays in children during the COVID-19 pandemic.